2021
DOI: 10.3390/molecules26195931
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of 6-Shogaol, an Active Compound of Ginger, in a Murine Model of Cisplatin-Induced Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a dose-limiting side effect of cisplatin therapy in cancer patients. However, effective therapies for cisplatin-induced AKI are not available. Oxidative stress, tubular cell death, and inflammation are known to be the major pathological processes of the disease. 6-Shogaol is a major component of ginger and exhibits anti-oxidative and anti-inflammatory effects. Accumulating evidence suggest that 6-shogaol may serve as a potential therapeutic agent for various inflammatory diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…In the present study, administration of oridonin decreased the amounts of 4-HNE and MDA in kidneys of cisplatin-injected mice. These molecules are well-known lipid peroxidation products and have been shown to be increased in cisplatin nephrotoxicity [ 34 , 35 ]. Moreover, cisplatin injection lowered the GSH/GSSG ratio, indicating increased oxidative stress [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, administration of oridonin decreased the amounts of 4-HNE and MDA in kidneys of cisplatin-injected mice. These molecules are well-known lipid peroxidation products and have been shown to be increased in cisplatin nephrotoxicity [ 34 , 35 ]. Moreover, cisplatin injection lowered the GSH/GSSG ratio, indicating increased oxidative stress [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess renal function, the serum concentrations of creatinine and blood urea nitrogen (BUN), two widely used indicators of kidney function [ 25 ], were measured. As shown in Figure 1 A,B, hispidulin administration significantly decreased the serum levels of creatinine (LPS, 0.80 ± 0.07 mg/dL vs. LPS + His, 0.52 ± 0.05 mg/dL, p < 0.01) and BUN (LPS, 120.8 ± 13.5 mg/dL vs. LPS + His, 71.1 ± 9.6 mg/dL, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Serum creatinine and BUN levels were measured to assess kidney function. These indicators are widely used in animal experiments to evaluate kidney function [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. We found that hispidulin significantly attenuated the LPS-induced renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the LPS-induced neutrophil infiltration was inhibited by carnosic acid (p < 0.001; Figure 5A,B). We also performed IHC staining for F4/80, a macrophage marker [23], on kidney sections to examine macrophage infiltration into the kidney. The number of F4/80-positive cells was increased after LPS injection, which was reduced by carnosic acid (p < 0.05; Figure 5C,D).…”
Section: Carnosic Acid Attenuated Lps-induced Inflammatory Responsesmentioning
confidence: 99%